MEANS OF DESCRIBING THE HUMAN PSYCHE IN ENGLISH AND UZBEK PHRASEOLOGY - Esirgapov Muhiddin; Mirzaeva Ruxshoda; Yokubov Anvar (International Engineering Journal For Research & Development, 2022)
By the beginning of the twentieth century, much attention has been paid to the scientific study of the phraseological complex of languages. As a result of research in this area, phraseology has been established as a separate branch of linguistics. This situation requires a more extensive study of the phraseology that is widely used in speech. The linguistic image of a person can be revealed on the basis of the parameters of its manifestation: biological, physical, mental, intellectual, social. Many researchers refer to any particular aspect in describing the concept of “person”: appearance, age, physical condition, mental state, social status, work activity, behavior, ethical relationships, and moral values, among others. That is why in this article we have devoted to the phraseological units that reveal the human psyche.